Moving Imagination: Explorations of Gesture and Inner Movement - De Preester, Helena (Amsterdam; Philadelphia John Benjamins, 2013)
This volume brings together contributions by philosophers, art historians and artists who discuss, interpret and analyse the moving and gesturing body in the arts. Broadly inspired by phenomenology, and taking into account insights from cognitive science, the contribution of the motor body in watching a film, attending a dance or theatre performance, looking at paintings or drawings, and listening to music is explored from a diversity of perspectives. This volume is intended for both the specialist and non-specialist in the fields of art, philosophy and cognitive science, and testifies to the burgeoning interest for the moving and gesturing body, not only in the creation but also in the perception of works of art. Imagination is tied to our capacity to silently resonate with the way a work of art has been or is created.